2022
DOI: 10.1590/1516-4446-2020-1133
|View full text |Cite
|
Sign up to set email alerts
|

Anger and substance abuse: a systematic review and meta-analysis

Abstract: Objective: Conduct a systematic review and meta-analysis to evaluate levels of anger among substance users compared to non-user controls and to analyze the possible association between anger and psychoactive substance use (PSU). Methods: The procedures of this review followed the Meta-Analyzes of Observational Studies in Epidemiology (MOOSE) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Four electronic databases (MEDLINE, EMBASE, BIREME, PsycINFO) were searched. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 75 publications
0
3
0
1
Order By: Relevance
“…Recent prevalence studies have highlighted the increase in cocaine use in Ireland and identified the emergence of ‘crack’ cocaine use among a marginalised population that may previously have used heroin [ 23 ]. Cocaine use can cause intense craving [ 37 ], with users also experiencing irritability and anxiety [ 38 ]. There is a need to investigate whether such behavioural issues are discouraging pharmacies from engaging with the needle exchange service.…”
Section: Discussionmentioning
confidence: 99%
“…Recent prevalence studies have highlighted the increase in cocaine use in Ireland and identified the emergence of ‘crack’ cocaine use among a marginalised population that may previously have used heroin [ 23 ]. Cocaine use can cause intense craving [ 37 ], with users also experiencing irritability and anxiety [ 38 ]. There is a need to investigate whether such behavioural issues are discouraging pharmacies from engaging with the needle exchange service.…”
Section: Discussionmentioning
confidence: 99%
“…However, anger and irritability can be present in other mental health conditions and personality disorders. A recent meta-analysis showed higher rates of anger scores among psychoactive substance users when compared to non-users ( 108 ). This finding highlights the relevance of anger in the evaluation and treatment of addiction.…”
Section: Six Main Transdiagnostic Dimensions Of Dysregulation Derived...mentioning
confidence: 99%
“…çalışmasında, psikoaktif madde kullanan bireylerin kullanmayanlara kıyasla daha yüksek düzeyde öfkeye sahip olduğunu ortaya koymuş ve tedavi programlarında öfke yönetiminin de ele alınmasını önermiştir (35). Ayrıca, madde kullanımı bireyleri intihar davranışına itmektedir (4).…”
Section: Psikiyatrik Ve Psikolojik Sorunlarunclassified